1957
DOI: 10.1113/jphysiol.1957.sp005756
|View full text |Cite
|
Sign up to set email alerts
|

The role of the antidiuretic hormone during water deprivation in rats

Abstract: It has been suggested that the survival of animals deprived of water is in direct proportion to their ability to concentrate their urine, and that the high concentration of their urine is achieved at the expense of an increased secretion of the antidiuretic hormone. The problem investigated here was to see whether the decrease of the urinary volume observed in laboratory rats deprived of water was the sole factor in the mechanism of water preservation and if so, whether the reduction of urinary secretion was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

1957
1957
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 23 publications
2
29
2
Order By: Relevance
“…The errors of the method fell within the limits stated previously (Dicker & Nunn, 1957). Nephrectomy and evisceration were performed on rats under ethanol anaesthesia, induced by the administration of 5 ml./100 g of a 12% (v/v) ethanol solution, and maintained, if necessary, by intravenous injections of 1 ml.…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…The errors of the method fell within the limits stated previously (Dicker & Nunn, 1957). Nephrectomy and evisceration were performed on rats under ethanol anaesthesia, induced by the administration of 5 ml./100 g of a 12% (v/v) ethanol solution, and maintained, if necessary, by intravenous injections of 1 ml.…”
Section: Methodssupporting
confidence: 55%
“…In four similar experiments the mean pressor activity of the urine of the second 'recipient' eviscerated rats was 4-7 + 0-82 % of the urinary pressor activity infused (Table 3). As the injection of urine does not affect the excretion of vasopressin simultaneously administered (Dicker & Nunn, 1957), these results suggested that the 'recipient' eviscerated rat dealt with the pressor activity of the urine from the eviscerated 'donor' in the same way as the latter had done with infused vasopressin. This was also suggested by the following experiment: four eviscerated rats were each infused with 1000 m-u.…”
Section: Resultsmentioning
confidence: 89%
“…2), when maximum osmolality reached was 4560 with a mean of 3300 m-osmole/kg. The dehydration was not continued for a longer period as it has been shown (Dicker & Nunn, 1957) that the maximum urine osmolality is achieved 72 hr after water withdrawal.…”
Section: Resultsmentioning
confidence: 99%
“…The latter has been shown to raise the concentration of the urine, even in the absence of vasopressin, in the dog (del Greco & de Wardener, 1956;Berliner & Davidson, 1957) and in the rat (Dicker, 1957). However, vasopressin administration alone will not increase the urinary concentration to the same extent as that found with dehydration in man (West, Traeger & Kaplan, 1955;Jones & de Wardener, 1956;Epstein, Kleeman & Hendrikx, 1957), dog (West et al 1955) or rat (Dicker & Nunn, 1957). Recently, Atherton et al (1971 a) have demonstrated that hydropenia combined with vasopressin resulted in a somewhat higher sodium concentration than vasopressin infusion alone in the medulla of the conscious Wistar rat.…”
Section: Discussionmentioning
confidence: 99%
“…Rats subjected to 8 days of saline imbibition reacted similarly to those on dry diet and the change.s observed in both groups were not significantly different from those of the water deprivation studies on the rat by Dicker and Nunn (1957); Jones and Pickering (1969);Bridges (1970) ;Castel and Abraham (1972) and Guzek. Orlowska-Majdak and Wdzieczak (1976).…”
Section: Discussionmentioning
confidence: 66%